2008
DOI: 10.1002/jso.21143
|View full text |Cite
|
Sign up to set email alerts
|

Radio guided occult lesion localization (ROLL) for non‐palpable invasive breast cancer

Abstract: The ROLL procedure seems to be an alternative to WGL in patients with non-palpable breast carcinoma. To determine the place of ROLL versus WGL in the treatment of non-palpable breast cancer, a randomized clinical trial is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 32 publications
3
13
0
Order By: Relevance
“…After intratumoral injection, more of the internal mammary chain LNs can be found thereby affecting the adjuvant therapeutic plan and possibly long-term survival [ 17 , 18 ]. In addition, injecting intratumorally allows lumpectomy with the radioguided occult lesion localization (ROLL) technique in the same procedure [ 19 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…After intratumoral injection, more of the internal mammary chain LNs can be found thereby affecting the adjuvant therapeutic plan and possibly long-term survival [ 17 , 18 ]. In addition, injecting intratumorally allows lumpectomy with the radioguided occult lesion localization (ROLL) technique in the same procedure [ 19 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rampaul et al concluded that ROLL was less painful for the patient and was an easier technique to perform surgically 107. Furthermore, the ROLL procedure could be combined with lymphatic mapping and sentinel lymph node biopsy, which makes it more patient-friendly compared with WGL 112,115. ROLL was reported to significantly reduce pre- and intraoperative localization time of nonpalpable breast tumors 3.…”
Section: Future Directionsmentioning
confidence: 99%
“…The simplest methods consist in implanting a foreign object ͑hook, clip, or gold rod 2 ͒ or injecting a marker near or inside the tumor. 3,4 These invasive procedures require puncturing the skin and are limited to accessible locations. Moreover, guiding tools do not determine the outline of the tumor, but rather its approximate position.…”
Section: Introductionmentioning
confidence: 99%